Psychological and pedagogical support of children in case of parental separation (age features) - Lіubov Shpilchak (Vasyl Stefanyk Precarpathian National University, 2018)
The article reveals the contents of psychological and pedagogical support of children from different age groups in parental separation. Separation of spouses as a legislation norm is analysed; the features of these distant families are highlighted; objectives for social teachers in this area of work are defined. Keywords: psychological and pedagogical support of children from distant families, separation, age features, social teachers.